2022
DOI: 10.1371/journal.pone.0270695
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up PET/CT of alveolar echinococcosis: Comparison of metabolic activity and immunodiagnostic testing

Abstract: Purpose To investigate the potential role of follow-up 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in therapy control of inoperable patients with alveolar echinococcosis. Materials and methods In this single-center retrospective cohort study, 48 PET/CT of 16 patients with confirmed alveolar echinococcosis were analysed. FDG-uptake of the most active echinococcosis manifestation was measured (i.e., maximum standardized uptake value (SUVmax) and in relation to backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Total IgE, parasite-specific IgE, IHA IgG titers, and Em2 + status changed significantly with increasing PNM stage. A respective correlation of serology (crude antigen preparations or the recombinant/purified antigens EM10, Em18, and Em2 + antigens) and the PNM stage has been shown previously [ 14 , 16 , 17 , 18 ] and was confirmed in our investigation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Total IgE, parasite-specific IgE, IHA IgG titers, and Em2 + status changed significantly with increasing PNM stage. A respective correlation of serology (crude antigen preparations or the recombinant/purified antigens EM10, Em18, and Em2 + antigens) and the PNM stage has been shown previously [ 14 , 16 , 17 , 18 ] and was confirmed in our investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Data from Hotz et al (2022) revealed strong correlations for both Echinococcus IgG and recEm18 serology with FDG tracer uptake in PET/CT scans [ 16 ]. Recent studies combining FDG-uptake by PET with specific serology (mainly Em18-ELISA) showed promising results regarding the safety of an STI [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%